First water vapor measurement over Athens, Greece, obtained by a combined Raman-elastic backscatter lidar system - Papayannis, Alexandros D.; Tsaknakis, Georgios; Mamouri, Rodanthi-Elisavet (My University, 2008)
Water vapor is one of the most important greenhouse gases, since it causes about two third of the natural greenhouse effect of the Earth's atmosphere. To improve the understanding of the role of the water vapor in the atmosphere, extensive water vapor profiles with high spatio-temporal resolution are, therefore, necessary. A recently install ground-based Raman lidar system is used to perform systematic water vapor measurements in the lower troposphere (500-5000 m asl.) over Athens, Greece (37.9°N, 23.6°E, 200 m asl.) since September 2006. Water vapor mixing ratio measurements are retrieved from simultaneous inelastic H2O and N2 Raman backscatter lidar signals at 387 nm (from atmospheric N2) and 407 nm (from H2O). The lidar observations are intercompared with radiosonde data obtained at the "Hellinikon" airport (37. 54° N, 23.44° E, 15m asl.) by the Hellenic Meteorological Service (HMS). First preliminary results of the systematic intercomparison between water vapor profiles derived, simultaneously, by our Raman lidar and by the HMS radiosondes are presented and show that the absolute differences generally remain less than 10% up to 5000 m height. Selected cases of water vapor vertical distributions in the troposphere are presented extensively and discussed, in conjunction with water vapor data obtained by the AIRS spaceborn sensors.
Keywords: Optical radar; Water vapor; Backscattering; Gases